Critical Epitopes in the Nucleocapsid Protein of SFTS Virus Recognized by a Panel of SFTS Patients Derived Human Monoclonal Antibodies - Yu, Li; Zhang, Li; Sun, Lina; Lu, Jing; Wu, Wei; Li, Chuan; Zhang, Quanfu; Zhang, Fushun; Jin, Cong; Wang, Xianjun; Bi, Zhenqiang; Li, Dexin; et al. (PLOS ONE, 2012)
Background SFTS virus (SFTSV) is a newly discovered pathogen to cause severe fever with thrombocytopenia syndrome (SFTS) in human. Successful control of SFTSV epidemic requires better understanding of the antigen target in humoral immune responses to the new bunyavirus infection. Methodology/Principal Findings We have generated a combinatorial Fab antibody phage library from two SFTS patients recovered from SFTSV infection. To date, 94 unique human antibodies have been generated and characterized from over 1200 Fab antibody clones obtained by screening the library with SFTS purified virions. All those monoclonal antibodies (MAbs) recognized the nucleocapsid (N) protein of SFTSV while none of them were reactive to the viral glycoproteins Gn or Gc. Furthermore, over screening 1000 mouse monoclonal antibody clones derived from SFTSV virions immunization, 462 clones reacted with N protein, while only 16 clones were reactive to glycoprotein. Furthermore, epitope mapping of SFTSV N protein was performed through molecular simulation, site mutation and competitive ELISA, and we found that at least 4 distinct antigenic epitopes within N protein were recognized by those human and mouse MAbs, in particular mutation of Glu10 to Ala10 abolished or significantly reduced the binding activity of nearly most SFTS patients derived MAbs. Conclusions/Significance The large number of human recombinant MAbs derived from SFTS patients recognized the viral N protein indicated the important role of the N protein in humoral responses to SFTSV infection, and the critical epitopes we defined in this study provided molecular basis for detection and diagnosis of SFTSV infection.